Mobilni telefon in pospešena kultura - Luthar, Breda (Javnost (Ljubljana), 2007)
The article argues for the greater emphasis on materiality and prosthetic nature of the mobile phone and for overcoming the divide between materiality and sociality in research on media technologies and on consumer or material culture in general. In order to understand the impact of "mobile turn" on the structure of feeling and on power relations in contemporary capitalism, the mobile phone's undiscoursive materiality should be explored. The author therefore argues for a move away from treatment of the mobile phone as the metaphoric representation of social relations (of class divisions, of cultural differentiation, of generational differences.) towards the investigation of its thingness and its performative role in framing contemporary sociality which is increasingly objects-centered.
Keywords: komuniciranje; communication; medosebne komunikacije; mobilni telefoni; simboli; symbol; družbeno vedenje